Evaluation of a plant-herbivore system in determining potential efficacy of a candidate biological control agent, cornops aquaticum for water hyacinth, eichhornia crassipes - Bownes, Angela (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2009)
Water hyacinth, Eichhornia crassipes Mart. Solms-Laubach (Pontederiaceae), a freefloating aquatic macrophyte of Neotropical origin, was introduced into South Africa as an ornamental aquarium plant in the early 1900's. By the 1970's it had reached pest proportions in dams and rivers around the country. Due to the sustainability, cost efficiency and low environmental risk associated with biological control, this has been a widely used method in an attempt to reduce infestations to below the threshold where they cause economic and ecological damage. To date, five arthropod and one pathogen biocontrol agents have been introduced for the control of water hyacinth but their impact has been variable. It is believed that their efficacy is hampered by the presence of highly eutrophic systems in South Africa in which plant growth is prolific and the negative effects of herbivory are therefore mitigated. It is for these reasons that new, potentially more damaging biocontrol agents are being considered for release. The water hyacinth grasshopper, Cornops aquaticum Brüner (Orthoptera: Acrididae), which is native to South America and Mexico, was brought into quarantine in Pretoria, South Africa in 1995. Although the grasshopper was identified as one of the most damaging insects associated with water hyacinth in its native range, it has not been considered as a biocontrol agent for water hyacinth anywhere else in the world. After extensive host-range testing which revealed it to be safe for release, a release permit for this candidate agent was issued in 2007. However, host specificity testing is no longer considered to be the only important component of pre-release screening of candidate biocontrol agents. Investigating biological and ecological aspects of the plant-herbivore system that will assist in determination of potential establishment, efficacy and the ability to build up good populations in the recipient environment are some of the important factors. This thesis is a pre-release evaluation of C. aquaticum to determine whether it is sufficiently damaging to water hyacinth to warrant its release. It investigated interactions between the grasshopper and water hyacinth under a range of nutrient conditions found in South African water bodies as well as the impact of the grasshopper on the competitive performance of water hyacinth. Both plant growth rates and the response of water hyacinth to herbivory by the grasshopper were influenced by nutrient availability to the plants. The ability of water hyacinth to compensate for loss of tissue through herbivory was greater under eutrophic nutrient conditions. However, a negative linear relationship was found between grasshopper biomass and water hyacinth performance parameters such as biomass accumulation and leaf production, even under eutrophic conditions. Water hyacinth's compensatory ability in terms of its potential to mitigate to detrimental effects of insect feeding was dependent on the amount of damage caused by herbivory by the grasshopper. Plant biomass and the competitive ability of water hyacinth in relation to another freefloating aquatic weed species were reduced by C. aquaticum under eutrophic nutrient conditions, in a short space of time. It was also found that grasshopper feeding and characteristics related to their population dynamics such as fecundity and survival were significantly influenced by water nutrient availability and that environmental nutrient availability will influence the control potential of this species should it be released in South Africa. Cornops aquaticum shows promise as a biocontrol agent for water hyacinth but additional factors that were not investigated in this study such as compatibility with the South African climate and the current water hyacinth biocontrol agents need to be combined with these data to make a decision on its release. Possible management options for this species if it is to be introduced into South Africa are discussed.
Keywords: Water hyacinth -- Control -- South Africa; Eichhornia crassipedes; Pontederiaceae; Grasshoppers; Biological pest control agents -- South Africa; Weeds -- Biological control -- South Africa; Invasive plants -- Biological control -- South Africa